Deleuze’s reading of the Critique of Pure Reason - Pachilla, Pablo (Estudios de Filosofía, 2022)
The aim of this paper is to provide an analysis of Gilles Deleuze’s interpreta- tion of the Critique of Pure Reason such as it appears in his 1963 monographic work La Philosophie critique de Kant. We will show that the originality of Deleuze’s reading lies in reading the critical project in retrospect, taking the sensus communis problem from the Critique of the Power of Judgment and applying it to the first Critique. In so doing, he points out the survival of a pre-established harmony, now interiorized, both between heterogeneous faculties and between the matter of phenomena and the Ideas of reason. This implies a reinterpretation of the critical project that has passed unnoticed within Kantian studies and that places the Third Critique as the ground of the previous ones, unveiling common sense as a condition of possibility of knowledge.